Thrombin potently enhances swelling-sensitive glutamate efflux from cultured astrocytes - Ramos-Mandujano, Gerardo; Vázquez-Juárez, Erika; Hernández-Benítez, Reyna; Pasantes-Morales, Herminia (Glia, 2007)
High concentrations of thrombin (Thr) have been linked to neuronal damage in cerebral ischemia and traumatic brain injury. In the present study we found that Thr markedly enhanced swelling‐activated efflux of 3H‐glutamate from cultured astrocytes exposed to hyposmotic medium. Thr (0.5–5 U/mL) elicited small 3H‐glutamate efflux under isosmotic conditions and increased the hyposmotic glutamate efflux by 5‐ to 10‐fold, the maximum effect being observed at 15% osmolarity reduction. These Thr effects involve its protease activity and are fully mimicked by SFFLRN, the synthetic peptide activating protease‐activated receptor‐1. Thr potentiation of 3H‐glutamate efflux was largely dependent on a Thr‐elicited increases in cytosolic Ca2+ (Ca2+i) concentration ([Ca2+]i). Preventing Ca2+i rise by treatment with EGTA‐AM or with the phospholipase C blocker U73122 reduced the Thr‐increased glutamate efflux by 68%. The protein kinase C blockers Go6976 or chelerythrine reduced the Thr effect by 19%–22%, while Ca/calmodulin blocker W7 caused a 63% inhibition. In addition to this Ca2+‐sensitive pathway, Thr effect on glutamate efflux also involved activation of phosphoinositide‐3 kinase (PI3K), since it was reduced by the PI3K inhibitor wortmannin (51% inhibition). Treating cells with EGTA‐AM plus wortmannin essentially abolished Thr‐dependent glutamate efflux. Thr‐activated glutamate release was potently inhibited by the blockers of the volume‐sensitive anion permeability pathway, NPPB (IC50 15.8 μM), DCPIB (IC50 4.2 μM). These results suggest that Thr may contribute to the excitotoxic neuronal injury by elevating extracellular glutamate release from glial cells. Therefore, this work may aid in search of neuroprotective strategies for treating cerebral ischemia and brain trauma. © 2007 Wiley‐Liss, Inc.